Changes in the physicochemical properties and volatile flavor compounds of dry‐cured Chinese Laowo ham during processing. Issue 8 (9th June 2020) - Wu, Weihang; Zhou, Yang; Wang, Guiying; Zhu, Renjun; Ge, Changrong; Liao, Guozhou
Abstract: In this work, physico‐chemical, lipolytic, free amino acids, and volatile flavor compounds changes that occur during the processing of Laowo ham were observed. Moisture content, water activity, trimethylamine‐ nitrogen (TMA‐N), and luminosity value ( L *) decreased significantly ( p < .05) from 74.74%, 0.90, 22.33 mg/kg, and 51.92 to 55.66%, 0.74, 10.40 mg/kg a, nd 39.88, respectively. Chloride content, pH, thiobarbituric acid (TBARS) value, peroxide value (POV), nitrite residue, and yellowness value ( b *) increased significantly ( p < .05) from 0.17%, 5.69, 0.06 mg/100 g, 0.03 g/100 g, 0.52 mg/kg, and 2.29 to 9.26%, 6.10, 0.33 mg/100 g, 0.10 g/100 g, 1.00 mg/kg, and 5.13, respectively. Eleven kinds of free fatty acids were identified. The content of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) increased during processing. The total amount of free amino acids increased significantly ( p < .05) from 4.94 mg/g to 87.89 mg/g. About 115 volatile compounds were identified.In the final products, alcohols and hydrocarbons became the dominant volatile compounds. Practical applications: Laowo ham is one of the most popular dry‐cured hams in southwest China's Yunnan province. At present, there are few studies on the changes in physicochemical properties and volatile flavor compounds in Laowo ham during processing, and the mechanism of flavor formation is still unknown. Therefore, the aim of the present study was to investigate the changes in physicochemical properties and flavor in Laowo ham during the production. These results contribute to a more accurate understanding of the quality changes in Laowo ham during processing and help to improve the product quality and optimize the duration of processing in the future.